Study on inflammation and fibrogenesis in MAFLD from 2000 to 2022: a bibliometric analysis - Luo, Kuanhong; Chen, Yang; Fang, Shuzheng; Wang, Siqi; Wu, Zhixin; Li, Huiqing (Frontiers in Endocrinology, 2023)
Chronic inflammation and fibrosis are significant factors in the pathogenesis of metabolic-associated fatty liver disease (MAFLD). In this study, we conducted a bibliometric analysis of publications on inflammation and fibrogenesis in MAFLD, with a focus on reporting publication trends. Our findings indicate that the USA and China are the most productive countries in the field, with the University of California San Diego being the most productive institution. Over the past 23 years, Prof. Diehl AM has published 25 articles that significantly contributed to the research community. Notably, the research focus of the field has shifted from morbid obesity and adiponectin to metabolic syndrome, genetics, and microbiome. Our study provides a comprehensive and objective summary of the historical characteristics of research on inflammation and fibrogenesis in MAFLD, which will be of interest to scientific researchers in this field.